Participatory design of a thematic questionnaire in the field of victimization studies. (March 2019) - Valente, Riccardo; Crescenzi Lanna, Lucrezia; Chainey, Spencer
The paper introduces the results of a two-step process that led to the design of a new questionnaire in the field of victimization studies. A desk-based review of national Crime and Victimization Surveys from five EU countries was performed and resulted in identifying opportunities to improve the consistency among these surveys as well as the need to include more independent variables in order to measure fear of crime and its correlation with sociological variables. Then 12 experts in survey-based measures of crime-related issues were involved in a Delphi panel with the objective of enhancing a participatory design of a new questionnaire addressing individual and space-based determinants of the perception of insecurity, which has been poorly explored to date.